THE ASSESSMENT OF SERUM ADROPIN AND CATALASE LEVELS IN PATIENTS WITH ALZHEIMER'S DISEASE: ADROPIN AND CATALASE LEVELS IN PATIENTS WITH ALZHEIMER'S DISEASE - Şimşek, Fatma; Aktaş, Yunus Emre; Gündoğdu, Ömer Lütfi; Kızıltunç, Ahmet (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Dementia is a disease that renders performing activities of daily living difficult and has a high cost of treatment. Objective: In this context, this study was conducted to assess the adropin and catalase levels, the relationship between adropin and catalase levels, and the roles of adropin and catalase in treatment in patients diagnosed with Alzheimer's type dementia. Methods: This observational analytical study's sample consisted of 30 patients with Alzheimer’s disease (AD). Thirty individuals without dementia whose age and gender characteristics matched those with AD were included in the control group. The adropin and catalase levels in the serum samples collected from both patient and control groups were analyzed. Results: Adropin and low-density lipoprotein cholesterol (LDLC) levels were notably elevated in patients with Alzheimer's disease (AD). In contrast, levels of vitamin D, albumin, and catalase were significantly reduced in these patients. Additionally, there was no meaningful correlation between the mini-mental state examination (MMSE) scores and the results of laboratory tests in individuals with AD. Additionally, it was determined that MMSE scores were positively correlated with adropin levels and negatively correlated with catalase levels. However, both correlations were statistically insignificant. Conclusion: The low levels of catalase in patients with AD support the important role of oxidative stress in the disease. The high levels of adropin in these patients suggest that adropin acts as a defense mechanism for the body. Catalase and adropin can be used as biomarkers in the diagnosis of AD, but they are not suitable biomarkers for assessing cognitive functions.